Human and Animal Trespass as Protest: Space and Continuity in Rural Somerset and Dorset. (20th February 2019) - Baker, Leonard
Abstract: Trespass was perhaps the most widespread illegal activity in nineteenth-century rural England and yet it has been critically understudied by historians. This period witnessed increasing attempts by landowners and authorities to privatise the landscape and so even the act of walking became politicised. This article examines how trespass served to contest both the physical arrangement of acts such as enclosure as well as the new uses that land was being put to. The placement of a human or animal body in a disputed field both physically and symbolically reshaped the landscape. Their presence performatively reconstructed the way the world once was; whilst their bodies dismantled the walls, hedges and fences which attempted to reshape rural life. Far from being an inert or merely economic activity, trespass was deployed in both communal feuds and attempts to assert the "correct" relationship between man, beast and environment. Trespass was an important and multifaceted tool for nineteenth-century protest, deployed by every stratum of society. However, fundamental differences between bodies; such as class, species, gender and physical ability, crucially differentiated how trespass was performed and punished. The specificity of the body involved in trespass is, consequently, key to understanding what trespass does politically.